Inductive effects of 10 and 12-vertex closo-carborane anions: cluster size and charge make a difference. Issue 9 (15th December 2015) - Estrada, Jess; Lugo, Christopher A.; McArthur, Scott G.; Lavallo, Vincent
Abstract : The inductive effects of 10 and 12-vertex closo -carborane anion ligand substituents are elucidated for the first time. It is found that both of these cluster substituents are potent electron donating groups, which is in contrast to C-functionalized o -carborane. The fact that the 10-vertex cluster displays the strongest electron donating ability can be rationalized by its charge and size. Abstract : A phosphine containing a 10-vertex carborane anion substituent and its subsequent ligation to a Rh(i ) carbonyl complex is reported. The complex is characterized by NMR spectroscopy and a single crystal X-ray diffraction study. In addition, the inductive effects of both 10 and 12 vertex C-functionalized closo -carborane anions are elucidated via I.R. analysis of the CO stretching frequencies of two Rh carbonyl complexes. Unlike C-functionalized neutral o -carborane the 10 and 12-vertex carborane anions are both strong electron donor substituents.